Safety culture: the Nottingham Veterinary Safety Culture Survey (NVSCS) - Oxtoby, C.; Mossop, Liz; White, Kate; Ferguson, Eamonn (BMJ Publishing Group, 2017)
Safety culture is a vital concept in human healthcare because of its influence on staff behaviours in relation to patient safety. Understanding safety culture is essential to ensure the acceptance and sustainability of changes, such as the introduction of safe surgery checklists. While widely studied and assessed in human medicine, there is no tool for its assessment in veterinary medicine. This paper therefore presents initial data on such an assessment: the Nottingham Veterinary Safety Culture Survey (NVSCS). 350 pilot surveys were distributed to practising vets and nurses. The survey was also available online. 229 surveys were returned (65 per cent response rate) and 183 completed online, resulting in 412 surveys for analysis. Four domains were identified: (1) organisational safety systems and behaviours, (2) staff perceptions of management, (3) risk perceptions and (4) teamwork and communication. Initial indications of the reliability and the validity of the final survey are presented. Although early in development, the resulting 29-item NVSCS is presented as a tool for measuring safety culture in veterinary practices with implications for benchmarking, safety culture assessment and teamwork training.